The Quran’s View on Body Positivity: Thematic Interpretation Study - Nabih, M. Nabih Zaky Al-Fikri; Agus Imam Kharomen; Leni Nur Azizah (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
The rising body image crisis in the digital era has led to serious consequences, including mental health issues, low self-esteem, and self-harm, particularly among youth. In response to beauty standards shaped by popular culture, the body positivity movement promotes self-acceptance and appreciation of physical diversity. However, its secular framing often overlooks spiritual aspects. This study explores the Qur’anic perspective on body positivity and how its values can foster spiritually grounded self-acceptance. Using a qualitative approach and thematic interpretation, relevant verses are analyzed, focusing on those concerning human creation, the prohibition of body denunciation, and gratitude for one’s physical form. The findings suggest that the Qur’an regards the human body as a perfect creation, opposes physical discrimination, and prioritizes piety over appearance. It promotes self-love rooted in gratitude and spiritual responsibility. These insights reveal that Islam provides a comprehensive ethical foundation for body positivity, offering a more holistic alternative to secular discourse.